2021
DOI: 10.1167/tvst.10.2.7
|View full text |Cite
|
Sign up to set email alerts
|

A Wide-Field Optical Coherence Tomography Normative Database Considering the Fovea-Disc Relationship for Glaucoma Detection

Abstract: Purpose One purpose of this study was to collect wide-field swept-source optical coherence tomography (SS-OCT) data from healthy eyes and build a wide-filed normative database. Another purpose was to compare the glaucoma diagnostic ability of new parameters based on this normative database to the parameters that are currently in use, such as the peripapillary retinal nerve fiber layer (RNFL), macular ganglion cell-inner plexiform layer, and ganglion cell complex (GCC) thickness. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The benefits of cluster analysis have been previously described by Yoshioka et al, 37 where age‐regression models of GCL thickness were far more apparent than when applying pointwise methods, and has since been applied to elucidate patterns of ageing in VFs and corneal parameters 31,43,61 and to optimise detection of pathological changes in VF and OCT results 32,62 . Additionally, cluster analysis allowed for the holistic incorporation of fovea to optic disc tilt into our models, which has been identified previously as a source of heterogeneity in GCIPL thicknesses in healthy cohorts that is likely to influence variability in pointwise analyses 39,63 . The relative preservation of sensitivity but improved specificity of clustered normative models, despite some loss of spatial information as a result of cluster‐based pooling, highlights the benefits of cluster analysis approaches in detection of GCIPL measurements corresponding to VF results with greater accuracy than conventional methods.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The benefits of cluster analysis have been previously described by Yoshioka et al, 37 where age‐regression models of GCL thickness were far more apparent than when applying pointwise methods, and has since been applied to elucidate patterns of ageing in VFs and corneal parameters 31,43,61 and to optimise detection of pathological changes in VF and OCT results 32,62 . Additionally, cluster analysis allowed for the holistic incorporation of fovea to optic disc tilt into our models, which has been identified previously as a source of heterogeneity in GCIPL thicknesses in healthy cohorts that is likely to influence variability in pointwise analyses 39,63 . The relative preservation of sensitivity but improved specificity of clustered normative models, despite some loss of spatial information as a result of cluster‐based pooling, highlights the benefits of cluster analysis approaches in detection of GCIPL measurements corresponding to VF results with greater accuracy than conventional methods.…”
Section: Discussionmentioning
confidence: 89%
“…32,62 Additionally, cluster analysis allowed for the holistic incorporation of fovea to optic disc tilt into our models, which has been identified previously as a source of heterogeneity in GCIPL thicknesses in healthy cohorts that is likely to influence variability in pointwise analyses. 39,63 The relative preservation of sensitivity but improved specificity of clustered normative models, despite some loss of spatial information as a result of cluster-based pooling, highlights the benefits of cluster analysis approaches in detection of GCIPL measurements corresponding to VF results with greater accuracy than conventional methods.…”
Section: Advantages Of Clustered Models Over Pointwise Methodsmentioning
confidence: 99%
“…4 ). Inbuilt normative databases do not incorporate a whole host of variables affecting inter-individual variations in GCIPL thickness, including but not limited to spherical equivalent refractive error and position of the optic disc relative to the fovea related to differences in trajectory of the papillomacular fibers, 33 35 which can translate to errors as highlighted in these examples. These findings highlight the pitfalls of overreliance on comparisons to normative databases, and reinforce the importance of interpreting these in conjunction with raw OCT data to arrive at accurate clinical assessments of pathological OCT findings.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for this, Chauhan and Burgoyne [ 59 ] proposed that both image acquisition and analysis should be performed according to the specific FoBMO axis of an individual to ensure the correct anatomical correspondence of all ONH, RNFL, and macular thickness measurements. Kim et al [ 60 ] confirmed the clinical value of FoBMO axis by applying a new wide-field normative database considering the Fovea-Disc relationship that significantly improved the diagnostic performance of DRI-OCT in Korean patients.…”
Section: Discussionmentioning
confidence: 98%